PENDAMPINGAN PENGEMBANGAN BAHAN AJAR LITERASI DAN NUMERASI BERBASIS ETHNOMATEMATIKA DI KKG KECAMATAN PANTI - Alfarisi, Ridho; Kristiana, Arika Indah; Arifandi, Agus; Fihrisi, Fathan (Jurnal Pengabdian Masyarakat Khatulistiwa, 2024)
ABSTRACTThere are three types of teacher activities that can be used with the independent learning platform, namely teaching, learning, and creating. These three activities can make the teacher a driving teacher. Based on PISA 2018, Indonesia occupies the top five positions from the bottom regarding language literacy, mathematics/numeration, and science. With the facts from the OECD, it indicates that there are problems that need to be resolved. Problems are not only in students, but also teachers and teaching materials developed. The results of Alfarisi, et al (2020) research show that the literacy level of students is still low because teachers are still unable to develop their potential in developing literacy and numeracy teaching materials. With the independent learning platform, it is hoped that it will become one of the teacher's facilities for learning and creating. Developing literacy and numeracy teaching materials cannot be separated from contextual objects, one of which is ethnomathematics. Teachers in the period of independent learning must be able to develop teaching materials that can be used to share materials with other teachers. Problems with teachers in the KKG Panti sub-district, Jember district include 1) developing ethnomathematics-based literacy and numeracy teaching materials, 2) compiling e-portfolios, and 3) there are no prospective driving teachers. One of the solutions offered is training and assistance in the preparation of teaching materials and e-portfolios. Based on these problems, the service team plans activities starting from training in preparing literacy and numeracy teaching materials based on local wisdom, assisting in the preparation of portfolios for prospective driving teachers, and the final evaluation regarding the development of teaching materials and portfolios.Keywords: Literacy, Numeracy, Ethnomatematics, Teaching Materials, MathematicsABSTRAKTerdapat tiga jenis kegiatan guru yang dapat digunakan dengan platform merdeka belajar yaitu mengajar, belajar, dan berkarya. Tiga kegiatan tersebut dapat menjadikan guru sebagai guru penggerak. Berdasarkan PISA 2018, Indonesia menempati posisi lima besar dari bawah terkait literasi Bahasa, matematika/numerasi, dan IPA. Dengan adanya fakta dari OECD, menandakan bahwa terdapat permasalahan yang perlu diselesakian. Permasalahan tidak hanya di siswa, tetapi juga guru dan bahan ajar yang dikembangkan. Hasil penelitian Alfarisi, dkk (2020) bahwa tingkat literasi siswa masih rendah disebabkan oleh guru masih belum bisa mengembangkan potensi dalam pengembangan bahan ajar literasi dan numerasi. Dengan adanya platform merdeka belajar diharapkan menjadikan salah satu fasilitas guru untuk belajar dan berkarya. Mengembangkan bahan ajar literasi dan numerasi tidak lepas dari objek kontekstual, salah satu objek kontekstual yaitu ethnomatematika. Guru di masa merdeka belajar harus dapat mengembangkan bahan ajar yang dapat digunakan bahan berbagi dengan guru yang lain. Permasalahan guru di KKG kecamatan Panti kabupaten Jember meliputi 1) pengembangan bahan ajar literasi dan numerasi berbasis ethnomatematika, 2) penyusunan e-portofolio, dan 3) belum ada calon guru penggerak. Salah satu solusi yang ditawarkan yaitu pelatihan dan pendampingan penyusunan bahan ajar dan e-portofolio. Berdasarkan permasalahan tersebut, tim pengabdi merencanakan kegiatan dimulai dari pelatihan penyusunan bahan ajar literasi dan numerasi berbsasis local wisdom, pendampingan penyusunan portofolio bagi calon guru penggerak, dan evaluasi akhir terkait pengembangan bahan ajar dan portofolio.Kata Kunci : Literasi, Numerasi, Ethnomatematika, Bahan Ajar, Matematika